Species diversity, abundance, and biomass of fish at offshore platforms in the Arabian Gulf - Sørensen, Johan Mølgård; Torquato, Felipe; Faulkner, Lauren; Lowe, Christopher G.; Carrara, Mathieu; Godina, Alexei; Al-Jamali, Fahad; Ben-Hamadou, Radhouan; Møller, Peter Rask; Range, Pedro (Frontiers in Marine Science, 2025)
Documented biodiversity associated with offshore oil and gas platforms has led to growing interest in their potential conversion to artificial reefs under Rigs-to-Reefs (RTR) programmes following decommissioning. In this study, we assessed fish assemblages associated with offshore platforms in Qatar’s Al Khalij oilfield for the first time, using remotely operated vehicle (ROV) video surveys. Species diversity, abundance, and biomass were quantified across depth gradients by surveying the full water column around two platforms. A total of 4,474 fishes were recorded, representing 46 taxa, with Carangidae and Serranidae as the most diverse families, and Pinjalo pinjalo, Scomberoides commersonnianus, and Lutjanus argentimaculatus as the most abundant species. Estimated biomass reached 6,184 kg per platform. A clear vertical zonation in species composition was observed, with Carangidae dominating surface layers and Serranidae more prevalent near the seafloor. Structurally complex areas, such as crossbeams and base zones, were identified as local biodiversity hotspots. Notably, Cheilinus trilobatus was recorded for the first time in the Arabian Gulf. Comparisons with previous studies from Qatar’s Al Shaheen oilfield revealed differences in species composition, likely due to variation in platform structure, geographic location, and sampling design. These findings demonstrate the role of platforms as artificial reefs supporting diverse fish communities and highlight the limited knowledge of biodiversity associated with artificial structures in the region. They provide a valuable baseline to inform future RTR decisions in the Arabian Gulf.